A HISTORY OF THE AGILA IN ADO LOCAL GOVERNMENT AREA OF BENUE STATE - OCHOGA EDWIN OCHOGA; Imanah Sunday Omoafena (International Studies Journal)
The paper interrogated the origin, migration and settlement of the Agila people in Ado Local Government Area of Benue State. The paper traced the genealogy of the Agila people to two separate Progenitors. The study adopted the ‘Ago-the progenitor of ten clans in Agila” and ‘Osilagama the progenitor of two clans in Agila’ ’narratives. The paper has established that the Wukari and Idah traditions and customs were assimilated (inherited) from the onset. The Jukun and the Igala ‘Model of royalty’ custom is quite a true resemblance of the Agila chieftaincy institution. And as such, if Agila history must be told by mirroring image of realities, with these and other cultural correspondence with the Igala ‘Chieftaincy Model’, and Arekwu mystery; tracing the genealogy of Agila as a whole to Idah is by no means out of place. Thus, conclusion was reached that: Firstly, Agila is a product of the mystical efforts of both Ago and Osilagama and their descendants that have over the centuries made Agila unique culturally wise in Idomaland. Secondly, Ago’s lineage has be traced to the Oba of Benin who briefly lived with his mother in Idah the ancestry home of Osilagama and other Idoma groups, but they never co-habited together in Idah before they separately migrated and settled down in Agila at about the same time. Thirdly, their children and descendants apparently formed the twelve clans; fourthly, the socio-cultural stratifications existing among the clans regarding the chieftaincy institution, the Arekwu cults and other customs were collectively agreed by the two Progenitors to be fashioned after the Idah Model. Fifthly and finally, all the Agila clans have peacefully co[1]existed and practiced their rich and unique cultural heritage for centuries.